Risk factors for pulmonary infection in elderly patients with type 2 diabetes: A protocol for systematic review and meta-analysis. - Zhaoyang Wei; Wenhao Su; Hairong Jia; Luo Yang; Jiaqi Zhang; Yanru Wang (PLoS ONE)
Background Lung infection is a prevalent chronic consequence of diabetes. Abnormal blood sugar levels, vascular endothelial damage, and alterations in capillary permeability predispose diabetes patients to lung infections. Currently, there is no comprehensive review addressing the risk factors for lung infection in diabetes. Consequently, our objective is to conduct a systematic review of the existing risk factors for lung infection in diabetes and offer recommendations for the targeted enhancement of treatment strategies. Methods and analysis We will search five English literature databases (PubMed, Embase, Web of Science, CINAHL, and Cochrane Library) and 4 Chinese databases (CNKI, WanFang, SinoMed and VIP) since the founding of the database until December 01, 2024. We will perform a systematic examination and meta-analysis of cohort, case-control and cross-sectional studies to identify all population-based risk factors for diabetes patients with pulmonary infection. Two researchers will independently assess the publication, extract data, and evaluate the quality and potential biases present in the study. We will utilize RevMan 5.4 software and STATA 16.0 for data analysis. The included studies will be assessed using the Newcastle Ottawa Quality Assessment Instrument (NOS) and Agency for Healthcare Research and Quality (AHRQ). If the heterogeneity of the included studies is excessively high, we will perform subgroup and sensitivity analysis to identify probable sources of heterogeneity. The assessment of publication bias will be conducted using a funnel plot. Furthermore, we will employ the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach to assess the quality of evidence for each exposure and outcome of interest. Discussion This article introduces a research protocol to explore the influencing factors of pulmonary infection in diabetes. The results of this study will summarize the evidence of influencing factors of pulmonary infection in diabetes at present. We hope to provide reliable advice for clinicians to make decisions, so as to support the implementation of effective prevention strategies for diabetes pulmonary infection. Trial registration PROSPERO CRD42024606429.